Optimization of protease production by Bacillus licheniformis in Sugarcane bagasse using statistical experimental design - Rathakrishnan, P.; Nagarajan, P.; Rajeshkannan, R. (Research in Biotechnology, 2012)
Sugarcane bagasse, the residue obtained after extracting the sugar juice from sugarcane was tested for the production of protease under solid-state fermentation (SSF) using Bacillus licheniformis. The fermentation variables were selected in accordance with Plackett-Burman design and were further optimized via response surface methodological approach. Four significant variables (K2HPO4, Beef extract, NaNO3 and Glycine) were selected for the optimization studies. The optimum values for the selected variables were; K2HPO4 -0.3464g/gds, Beef extract- 0.1039g/gds, NaNO3- 0.0334g/gds and Glycine- 0.1027g/gds. A second-order model equation was suggested and then validated experimentally.The model adequacy was very satisfactory as the coefficient of determination was 0.95. The maximum protease production was 146.28U/gds